Tourism As Possible Opportunity To Address The Crisis In Italy - Dorel Nicolae Manitiu (European Regional Science Association (ERSA), 2013)
Since the 80s we have been facing a rising phase of the globalization process , based on the evolution of the American model of capitalism and on the emerging power of China and other developing countries. At global level technological innovation is crucial for triggering information revolution and making multinationals more competitive and innovative. If we look at average annual rates of growth in real terms, we can see the scale of the phenomenon. Globally, more and more countries fall barriers on foreign direct investment and portfolio investment. This situation favors the movement of capital and gives them greater mobility, thanks to technological advances and the revolution in communications systems. Thus the first application of the globalization phenomenon can be placed within the international currency markets, bonds and shares, savings and financial instruments operated by intermediaries for the purpose of funding agencies, states and businesses. The result of these international operations is 'speculation', whose purpose is not to finance the real economy but to make profit on transactions (Targetti, 2009). At the same time the tariff barriers have been cut down, not only among developed countries, but also between developed and developing countries, especially emerging powers. At this point, free trade is gaining more weight and global prices of manufactured goods are stabilizing, while the rules on capital movements are dwindling. This trend has created a favorable environment for the entry of new firms in the financial market overall, and new opportunities for consumers and investors. The result of these processes is represented by the entry of about three billion people in the circuit of production and distribution of wealth. Emerging powers has an increasing role in terms of both commercial and financial activities in the world economy. Among the negative aspects, we higlight inequality on income distribution, the increase of global environmental degradation the effects of financial instability on real economy. This paper analyses the insights on tourism development policies as a possibile answer to globalization and economic crisis. Firms operating in the tourism sector usually have limited access to innovative resources. Thus, volunteers organizations and governmental structures that are active in the tourism sector, should involve tourism in the innovation systems foreliminating seasonality, advancing technical and scientific knowledge, promoting the export of concepts, events, etc. and last but not least, rasing new funds for tourism, including EU funds, research and development projects and venture capital.
Keywords: R58; Q01; 330; tourism; crisis; development